1994
DOI: 10.1258/002367794781065870
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for the welfare of animals in rodent protection tests: A Report from the Rodent Protection Test Working Party

Abstract: The rodent protection test (RPT) is used in antimicrobial research to confirm the in vivo efficacy of novel antibacterial, antiviral and antifungal agents. The RPT may involve lethal infection and thus has the potential to cause significant suffering. These Guidelines recommend refinements to the RPT which reduce animal use to a minimum and suggest cardinal clinical signs which act as predictors of lethality. Early recognition of these signs is imperative to minimize suffering, allow identification of humane e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…At the end of the immunosuppression period the rats were sacrificed and P. carinii was recovered from their lungs. The research complied with national legislation, with company policy on the care and use of animals, and with related guidelines (1).…”
Section: Methodsmentioning
confidence: 99%
“…At the end of the immunosuppression period the rats were sacrificed and P. carinii was recovered from their lungs. The research complied with national legislation, with company policy on the care and use of animals, and with related guidelines (1).…”
Section: Methodsmentioning
confidence: 99%
“…The founding fathers of the three Rs summarized these points by saying "The greatest scientific experiments have always been the most humane and the most aesthetically attractive, conveying a sense of beauty and elegance which is the essence of science at its most successful" (3). Validating this idea, the Rodent Protection Test Working Party reported that the refinement of lethal infection models with nonlethal humane endpoints has "not affected the utility of the results obtained", although supporting data did not accompany the statement (9).…”
Section: The Pros and Cons Of Humane Endpoints In Shock Researchmentioning
confidence: 99%
“…Surprisingly, in some animals, weight loss reached 30 to 50% shortly before death. It was also found that body temperature (measured by transponders) always decreased; however, a significant change was observed only in the terminal stages of infection and so, unlike other studies (Acred et al 1994;Soothill et al 1992), body temperature was not a useful early discriminating parameter. It was important that staff observing the animals could reliably score their condition.…”
Section: Rabies Vaccine Potency Test: Examplementioning
confidence: 70%